Effectiveness of Iron and Folic Acid Supplementation Programs in Reducing Anemia during Pregnancy - Shafia Afridi, Asma Ambareen, Shagufta Naz, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the effectiveness of iron and folic acid supplementation in reducing anemia during pregnancy, with a particular focus on factors influencing adherence to supplementation among pregnant women in Pakistan. Methodology: A retrospective study was conducted from June 2020 to June 2021. Data were collected from 400 pregnant women, assessing adherence to supplementation, hemoglobin levels, and the presence of anemia. Logistic regression and chi-square tests were used to analyse the data. Results: The results showed that 280 (70.0%) participants adhered to iron and folic acid supplementation, while 160 (40.0%) were diagnosed with anemia. A significant relationship was found between adherence to supplementation and reduced anemia (p = 0.001). Logistic regression analysis revealed that women aged 31–40 years (p = 0.045), with higher hemoglobin levels (p = 0.004), who started antenatal care in the first trimester (p = 0.006), were more likely to adhere to supplementation. Comorbidities like hypertension (p = 0.028) and diabetes (p = 0.033) were associated with lower adherence rates. Conclusion: Adherence to iron and folic acid supplementation is a key factor in reducing anemia during pregnancy. Early antenatal care, maternal health status, and managing comorbidities are crucial for improving adherence. Future studies should involve larger, multicenter trials to validate these findings and refine healthcare interventions. Keywords: Anemia, Iron Deficiency, Folic Acid, Pregnancy, Adherence.